Young adolescents who combine alcohol and energy drinks have a higher risk of reporting negative behavioural outcomes - Holubcikova, Jana; Kolarcik, Peter; Madarasova Geckova, Andrea; Joppova, Eva; van Dijk, Jitse P; Reijneveld, Sijmen A (International journal of public health, 2017)
OBJECTIVES: To explore whether young adolescents consuming alcohol and energy drinks combined were more likely to report negative behavioural outcomes than their peers who drink only one type of these beverages or are abstinent. METHODS: We analysed data on a representative sample of Slovak adolescents 8502 adolescents (mean age 13.21, 49.4 % boys) from the 2014 Health Behaviour in School-aged Children cross-sectional study. We assessed the associations of alcohol and energy drinks consumption with negative outcomes and their potential synergy, as measured by the synergy index (SI). RESULTS: Adolescents consuming both alcohol and energy drinks were at higher risk of negative behavioural outcomes than their peers who drank only alcohol or energy drinks or were non-consumers. Consumers of alcohol and energy drinks were highly prone to be involved in fighting-the joint association of alcohol and energy drinks consumption was greater than sum of its associations separately in relation to fighting (SI 1.49; 95 % confidence interval 1.03-2.16). CONCLUSIONS: Preventive strategies should aim at increasing awareness of negative behavioural outcomes-especially aggressive behaviour associated with alcohol and energy drinks consumption among young adolescents.
Keywords: Humans; Risk; riziko; Self Report; zpráva o sobě; Energy drinks; dítě; energetické nápoje; Child; Energy Drinks; Alcohol Drinking; pití alkoholu; Female; lidé; Slovakia; Slovenská republika; Problem Behavior; ženské pohlaví; Male; problémové chování; Adolescent; vyrovnaná skupina; Cross-Sectional Studies; Peer Group; Alcohol; Negative behavioural outcomes; mužské pohlaví; Young adolescents; průřezové studie; mladiství